Nitrogen Loss Estimation Worksheet (NLEW): An Agricultural Nitrogen Loading Reduction Tracking Tool - Deanna L. Osmond; Lin Xu; Noah N. Ranells; Steve C. Hodges; Roger Hansard; Stephen H. Pratt (The Scientific World Journal)
The Neuse River Basin in North Carolina was regulated in 1998, requiring that all pollution sources (point and nonpoint) reduce nitrogen (N) loading into the Neuse Estuary by 30%. Point source N reductions have already been reduced by approximately 35%. The diffuse nature of nonpoint source pollution, and its spatial and temporal variability, makes it a more difficult problem to treat. Agriculture is believed to contribute over 50% of the total N load to the river. In order to reduce these N inputs, best management practices (BMPs) are necessary to control the delivery of N from agricultural activities to water resources and to prevent impacts to the physical and biological integrity of surface and ground water. To provide greater flexibility to the agricultural community beyond standard BMPs (nutrient management, riparian buffers, and water-control structures), an agricultural N accounting tool, called Nitrogen Loss Estimation Worksheet (NLEW), was developed to track N reductions due to BMP implementation. NLEW uses a modified N-balance equation that accounts for some N inputs as well as N reductions from nutrient management and other BMPs. It works at both the field- and county-level scales. The tool has been used by counties to determine different N reduction strategies to achieve the 30% targeted reduction.